2015
DOI: 10.1111/evo.12840
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected positive and negative effects of continuing inbreeding in one of the world's most inbred wild animals

Abstract: Inbreeding depression, the reduced fitness of offspring of related individuals, is a central theme in evolutionary biology. Inbreeding effects are influenced by the genetic makeup of a population, which is driven by any history of genetic bottlenecks and genetic drift. The Chatham Island black robin represents a case of extreme inbreeding following two severe population bottlenecks. We tested whether inbreeding measured by a 20-year pedigree predicted variation in fitness among individuals, despite the high me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 56 publications
1
20
1
Order By: Relevance
“…This could simply result from the inbred individuals not being exposed to the cost of raising fledglings (since they produced fewer offspring), although this is rather unlikely as even though helpers of both sexes and dominant males might not have sired offspring, they routinely take care of young on their home territory. A few other studies have reported positive associations between inbreeding and fitness components, which were suggested to be the result of these offspring inheriting a "proven genotype" (i.e., high quality genotype) from a highly inbred parent (Weiser et al 2016) or by purging and partial dominance of deleterious alleles (Moreno et al 2015). Despite the limited dispersal in our study population, purging is extremely unlikely as there is no evidence for a recent bottleneck.…”
Section: Inbreeding Depressionmentioning
confidence: 59%
See 1 more Smart Citation
“…This could simply result from the inbred individuals not being exposed to the cost of raising fledglings (since they produced fewer offspring), although this is rather unlikely as even though helpers of both sexes and dominant males might not have sired offspring, they routinely take care of young on their home territory. A few other studies have reported positive associations between inbreeding and fitness components, which were suggested to be the result of these offspring inheriting a "proven genotype" (i.e., high quality genotype) from a highly inbred parent (Weiser et al 2016) or by purging and partial dominance of deleterious alleles (Moreno et al 2015). Despite the limited dispersal in our study population, purging is extremely unlikely as there is no evidence for a recent bottleneck.…”
Section: Inbreeding Depressionmentioning
confidence: 59%
“…A few other studies have reported positive associations between inbreeding and fitness components, which were suggested to be the result of these offspring inheriting a “proven genotype” (i.e., high quality genotype) from a highly inbred parent (Weiser et al. ) or by purging and partial dominance of deleterious alleles (Moreno et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have found no such effects of inbreeding on direct measures of offspring survival (Kempenaers et al 1996;Kruuk et al 2002) or on other traits that could indirectly affect survival, such as the incidence of malformations in larval tiger salamanders (Ambystoma tigrinum tigrinum) (Williams et al 2008). Finally, somewhat surprisingly, a number of studies have found positive effects of inbreeding on offspring survival (Richardson et al 2004;Weiser et al 2016;Bichet et al 2018). Additionally, it is important to recognize sources of error in calculating effects of inbreeding, which can change across life stages.…”
Section: Introductionmentioning
confidence: 96%
“…We used Pearson correlation coefficients to identify and exclude highly correlated fixed effects prior to analysis and, in all but one case, dropped correlated fixed effects with coefficients ≥ 0.60 (Table S2). Location and inter-aviary distance were correlated at 0.79, but both were essential to include as predictors of reproductive success; thus, we retained them in our global GLMM and subsequently evaluated multicollinearity within the GLMM using variance inflation factors (VIF) to ensure that the covariates used in model averaging had VIF < 5 (e.g., Belsley et al, 1980;Weiser et al 2015). VIFs were calculated using the vif command from the car package (Fox & Weisberg, 2011).…”
Section: Methodsmentioning
confidence: 99%